1984
DOI: 10.1017/s0263593300013882
|View full text |Cite
|
Sign up to set email alerts
|

Early Palaeozoic metamorphic history of the Midland Valley, Southern Uplands–Longford-Down massif and the Lake District, British Isles

Abstract: A model for the early Palaeozoic metamorphic history of the Midland Valley and adjacent areas to the S in Scotland, England and Ireland is based on the results of new field mapping, thin section petrography, electron probe microanalysis, X-ray diffractometry, conodont and palynomorph colouration and graptolite reflectance measurement.The oldest metamorphic rocks of the Midland Valley of Scotland, excluding xenoliths in post-Silurian lavas, are possibly the blueschist occurrences in the melange unit of the Ball… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 59 publications
0
32
0
Order By: Relevance
“…All the ARD, KB samples, and NI samples have experienced prehnite-pumpellyite grade metamorphism (Oliver et al 1984), equivalent to anchizone metamorphism (Frey and Robinson 1999), resulting in the almost complete conversion of smectite to illite. Sample KB02 from Kirkcudbright was described by Merriman and Roberts (1990) as sample BRS289.…”
Section: Mineralogymentioning
confidence: 99%
“…All the ARD, KB samples, and NI samples have experienced prehnite-pumpellyite grade metamorphism (Oliver et al 1984), equivalent to anchizone metamorphism (Frey and Robinson 1999), resulting in the almost complete conversion of smectite to illite. Sample KB02 from Kirkcudbright was described by Merriman and Roberts (1990) as sample BRS289.…”
Section: Mineralogymentioning
confidence: 99%
“…see Molyneux, 1987). These rocks are highly disrupted by soft-sediment deformation structures and are of significantly lower metamorphic grade compared to the Silurian rocks in the adjacent coastal sections (Oliver et al 1984). This suggests that these rocks may have formed in a very shallow part of the thrust wedge where the effects of down-slope, gravity-induced deformation were dominant.…”
Section: B the Lower Palaeozoic Rocks Of Southeastern Scotlandmentioning
confidence: 99%
“…Rocks from the Llandovery/Wenlock inliers were analysed using XRD (Oliver et al 1984) and some con- The study showed the rocks regional metamorphic state lies between the zeolite and the prehnite-pumpellyite facies, that is, weak burial metamorphism. In addition, Colour Alteration Indices of conodonts from near Girvan and the Pentland Hills indicate temperatures up to 150 °C.…”
Section: A Metamorphismmentioning
confidence: 99%